Artificial Intelligence in Pre-University Education: What and How to Teach - Sara Guerreiro-Santalla; Francisco Bellas; Richard J. Duro (Proceedings, 2020)
The present paper is part of the European Erasmus+ project on educational innovation led by the UDC and entitled “AI+: Developing an Artificial Intelligence Curriculum adapted to European High School”. In this paper, the progress achieved during the first year of the project will be presented. Mainly, the definition of the methodological approach for this future subject has been defined, and the AI topics to be dealt with at this age have been established. It has been a great effort to select the most appropriate focus for this subject considering the students’ and teachers’ technical background and the schools’ equipment.